Specific Directions of the Digital Development of Industrial Production - Normuradov Nurbek Sunatulloyevich (Research Parks Publishers, 2022)
This article outlines views on the main and specific aspects of the digital development of industrial production. The main directions of the introduction of digital technologies in the production process and the organization of intelligent production were also discussed.